2019
DOI: 10.1055/s-0039-1692128
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric Outcomes in U.S. Veterans: Emerging Knowledge, Considerations, and Gaps

Abstract: In the post-9/11 era, the number of young women serving, and deploying, in the military grew rapidly; as they exit service, there is tremendous increase in reproductive-aged women Veterans. Here, we review the limited but growing research regarding Veterans' pregnancy and obstetric outcomes. U.S. women Veterans returning from deployment carry a high burden of physical and mental health conditions, and often trauma. As poor mental health is known to predict poorer maternal and infant sequelae, there are unique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Several risk factors for preterm birth (PTB) and LBW have been identified as prevalent in Veterans. [8][9][10] Compared to the general population, women Veterans have a higher prevalence of complex clinical (diabetes and hypertension) and mental health (depression, posttraumatic stress disorder [PTSD], and anxiety) comorbidities. 9,[11][12][13] Previous studies of the general population have concluded that increased maternal clinical comorbidities and advanced age are associated with PTB.…”
Section: Introductionmentioning
confidence: 99%
“…Several risk factors for preterm birth (PTB) and LBW have been identified as prevalent in Veterans. [8][9][10] Compared to the general population, women Veterans have a higher prevalence of complex clinical (diabetes and hypertension) and mental health (depression, posttraumatic stress disorder [PTSD], and anxiety) comorbidities. 9,[11][12][13] Previous studies of the general population have concluded that increased maternal clinical comorbidities and advanced age are associated with PTB.…”
Section: Introductionmentioning
confidence: 99%